The Effectiveness of Logo Design and Packaging form Towards the Buying Interest in Pisang Lumer and Aneka Keripik (Do’a Ibu) - Roszila, Roszila; Asrofillah, Muhammad Fuad (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
In an era of intense market competition, visual branding elements such as logo design and packaging form are critical for Micro, Small, and Medium Enterprises (MSMEs) to capture consumer attention and differentiate their products. This study addresses a specific gap in visual branding research within peripheral Indonesian markets by analyzing the effectiveness of logo design and packaging form on consumer buying interest for Pisang Lumer and Aneka Keripik (Do'a Ibu) in Bengkalis. Employing a quantitative methodology, primary data were collected through structured Likert-scale questionnaires distributed during the Polbeng Business Expo. Utilizing purposive sampling alongside Slovin’s formula, 171 valid responses were successfully gathered from an estimated population of 300 visitors who had directly interacted with the products. Following rigorous instrument quality and classical assumption tests, the data were evaluated using multiple linear regression analysis. The empirical results indicate that both visual branding elements exert a positive and statistically significant impact on purchasing interest. Specifically, logo design demonstrates a stronger, more dominant influence (β = 0.580, p < 0.001) compared to packaging form (β = 0.286, p < 0.001). Furthermore, the Adjusted R² value reveals that these variables collectively explain 64.4% of the variation in consumer buying interest. These findings strongly suggest that resource-constrained MSMEs should prioritize clear logo optimization alongside functional, consumer-aligned packaging to strengthen competitiveness and stimulate purchasing decisions.